Non-alcoholic fatty liver disease and metabolic syndrome in overweight adolescents - Moraes, Letícia Fregona Hungria de; Fernandes, Vânia de Fátima Tonetto; Salustriano, Ingrid Kelly Marinho; Reis, Giovana Belisário; Neto, Guido de Paula Colares; Figueiredo, Carolina Costa; Evangelista, Nara Michelle de Araújo; Masquio, Deborah Cristina Landi (O Mundo da Saúde, 2024)
Non-alcoholic fatty liver disease (NAFLD) is characterized by the accumulation of fat in the liver and may be associated with metabolic syndrome (MS). Metabolic syndrome is considered a cluster of metabolic alterations, including lipid, glycemic, and blood pressure disturbances, along with excess abdominal adiposity. The coexistence of these two conditions may predispose individuals to increased cardiovascular risk and mortality. The relevance of this study stands out in the Brazilian context, where the rising cases of NAFLD and MS in adolescents reflect a global trend but lack sufficient investigation into their interconnections within the national scenario. The objective of this study was to investigate the prevalence and relationship between NAFLD and MS in overweight adolescents, as well as to explore the magnitude of their association and the risk factors involved. A cross-sectional study with observational data analysis was conducted at a State Pediatric Hospital in São Paulo. The sample consisted of 67 adolescents aged 10 to 19 years, diagnosed as overweight. All participants underwent anthropometric evaluation, and biochemical and NAFLD data were collected from electronic medical records. For the diagnosis of metabolic syndrome (MS), the International Diabetes Federation criteria were used as a reference. In the total sample, the prevalence of NAFLD and MS was 47.8% and 53.1%, respectively. A significant association was observed between the presence of NAFLD and MS, with NAFLD being more prevalent in the group of adolescents with MS (63.9%) compared to the group without MS (39.1%). The presence of MS was associated with a 3.45 times higher likelihood of a NAFLD diagnosis. Adolescents with NAFLD had significantly higher values of weight, BMI, LDL cholesterol concentrations, and diastolic blood pressure compared to the group without NAFLD. Among the metabolic parameters, LDL cholesterol concentrations and BMI were associated with an increased likelihood of NAFLD. The findings of this study indicate a high prevalence of NAFLD and MS in overweight adolescents, as well as a significant association between these conditions, with particular emphasis on LDL cholesterol concentrations and BMI. Considering MS as a platform for the development of non-communicable chronic diseases and its association with hepatic steatosis, these findings serve as a warning for the adoption of preventive measures starting from the pediatric stage.